Doubled haploidy in model and recalcitrant species - Jose M. Segui-Simarro (Frontiers Research Topics, 2016)
Doubled haploids (DHs) are powerful tools to reduce the time and costs needed to produce pure lines to be used in breeding programs. DHs are also useful for genetic mapping of complex qualitative traits, to avoid transgenic hemizygotes, for studies of linkage and estimation of recombination fractions, for screening of recessive mutants. These are just some of the advantages that make DH technology one of the most exciting fields of present and future plant biotechnology. All of the DH methods have model species where these technologies have been developed, or that respond every efficiently to their corresponding induction treatment. However, not all the species of economical/agronomical interest respond to these methodologies as they should be in order to obtain DHs on a routine basis. Indeed, many of them are still considered as low-responding or recalcitrant to these treatments, including many of the most important crops worldwide. Although many groups are making significant progresses in the understanding of these intriguing experimental pathways, little is known about the origin, causes and ways to overcome recalcitrancy. It would be very important to shed light on the particularities of recalcitrant species and the special conditions they need to be induced. In parallel, the knowledge gained from the study of basic aspects in model species could also be beneficial to overcome recalcitrancy. In this e-book, we present a compilation of different approaches leading to the generation of DHs in model and in recalcitrant species, and different studies on new and relevant aspects of this process, useful to extract common traits and features, to know better these processes, and eventually, to elucidate how to make DH technology more efficient.